Behavioral Dynamics of Coastal Communities in Waste Disposal: A Review - Hartati Bahar; Waode Nur Aslin; Yuli Budiyanti (Journal of Health Science and Pharmacy, 2025)
Background: Improper waste management driven by human behavior poses a serious threat to the environment, particularly in coastal areas. Marine pollution caused by waste not only damages ecosystems but also adversely affects the economy, especially sectors dependent on marine resources. In addition to degrading the aesthetic value of coastal environments and generating unpleasant odors, unmanaged waste serves as a breeding ground for viruses, bacteria, and parasites that can lead to various health problems, including digestive disorders, infections, and skin diseases. Objective: This study aims to conduct a literature review to identify and analyze the causal factors influencing community behavior in waste disposal practices in coastal regions. Method: This article employs a literature review method. A total of 20 relevant articles were selected from the Google Scholar and Mendeley databases based on specific inclusion and exclusion criteria. The data were analyzed descriptively to identify recurring patterns and key findings. Results: The review reveals that improper waste disposal behavior in coastal areas persists largely due to low levels of education, which limits public understanding of appropriate waste management practices. This knowledge deficit influences individual attitudes and behaviors, particularly in managing household waste. Negative attitudes can hinder the acceptance of environmental information or guidance. Furthermore, the availability of waste management infrastructure plays a critical role in facilitating effective waste handling. Supervision by local authorities is also essential in curbing improper waste disposal practices in coastal communities. Conclusion: The persistence of improper coastal waste disposal behavior is influenced by several factors, including educational attainment, environmental knowledge, individual attitudes, the availability of waste management facilities, settlement characteristics, and regulatory oversight. Keywords: Health Knowledge, Attitudes, Educational Status, Coastal Waste, Indonesia.